Antimicrobial Activity of Leaves of Lantana camera Linn. - kaushik, rahul (International Journal of Pharmaceutical & Biological Archive, 2010)
The antimicrobial activity of extract from the leaves of Lantana camera Linn. were investigated against both gram positive and gram negative bacterial strains. Test bacteria was Staphylococcus aureus, Escherichia coli, Bacillus subtillus and Pseudomonas aeruginosa, all four are pathogenic bacteria that cause diarrhea and many more uncontrolled diseases due to resistance. Hydro alcoholic extract showed significant inhibitory effects against antibiotic resistant gram negative bacteria including E. coli and Pseudomonas aeruginosa. Antimicrobial activity was assayed by the standard disc diffusion method.